Design Strategies of Tumor‐Targeted Delivery Systems Based on 2D Nanomaterials. Issue 11 (26th September 2022) - Ding, Lin; Liang, Minli; Li, Chenchen; Ji, Xinting; Zhang, Junfeng; Xie, Weifen; Reis, Rui L.; Li, Fu‐Rong; Gu, Shuo; Wang, Yanli
Abstract: Conventional chemotherapy and radiotherapy are nonselective and nonspecific for cell killing, causing serious side effects and threatening the lives of patients. It is of great significance to develop more accurate tumor‐targeting therapeutic strategies. Nanotechnology is in a leading position to provide new treatment options for cancer, and it has great potential for selective targeted therapy and controlled drug release. 2D nanomaterials (2D NMs) have broad application prospects in the field of tumor‐targeted delivery systems due to their special structure‐based functions and excellent optical, electrical, and thermal properties. This review emphasizes the design strategies of tumor‐targeted delivery systems based on 2D NMs from three aspects: passive targeting, active targeting, and tumor‐microenvironment targeting, in order to promote the rational application of 2D NMs in clinical practice. Abstract : 2D nanomaterials (2D NMs) have unique structures and properties, which give them obvious advantages in precision targeted‐delivery systems for tumors. This review introduces the design strategies of 2D NMs for tumor targeted‐delivery therapy from three aspects: passive, active, and tumor microenvironment targeting, aiming to deepen the understanding of targeted‐therapy strategies and clinical applications of 2D NMs.